Rates of ever breastfeeding, early initiation, and exclusive breastfeeding in Saudi Arabia: a narrative review - Aldossary, Mohammed; AlAsmari, Bayan; Almuaddi, Afnan M Almuaddi; Alhajri, Shahad; El Dalatony, Mervat (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Breastfeeding is one of the most effective techniques to ensure favorable maternal and child health and survival. However, contrary to the World Health Organization (WHO) recommendations, global breastfeeding rates remain below the target. Aim: Hence, this review aimed to update and assess the reported rates of ever breastfeeding, early initiation of breastfeeding (EIBF), and exclusive breastfeeding (EBF) in recent Saudi Arabian studies (2018–2023). Methods: Data bases were searched for recent breastfeeding-related studies published between January 2018 and June 2023. This review comprised 18 cross-sectional studies. Results: The reported rates of ever breastfeeding ranged from 64.7% to 97.5%, and the EIBF rates ranged from 13.9% to 85.1%. In addition, 16.3%–45.7% of women practiced EBF for their infants’ first 6 months of life.Conclusions: Breastfeeding rates reported by women in various regions of Saudi Arabia are lower than the current WHO recommendations. Our results thus demonstrate the significant geographic and temporal data heterogeneity in breastfeeding practices in Saudi Arabia. Recommendations are made to enhance these rates.